Gossypin Suppresses Cell Growth by Cytotoxic Effect and Induces Apoptosis in MCF-7 Cells - ÇİÇEK, Mustafa; ÇINAR, İrfan; AKSAK, Selin (Medical Records - International Medical Journal, 2022)
Aim: Today, breast cancer is a disease that is encountered commonly in women with limited options for treatment. It is needed to find new agents that can be effective in preventing or managing this disease. It has been demonstrated that gossypin inhibits tumor growth. In our study, it has been targeted to examine the effects of gossypin regarding both anticancer activity and apoptosis in MCF-7 cells. Material and Method: MCF-7 cells were treated with different doses of gossypin and with 50 µM cisplatin for 24, 48, and 72 hours. The MTT analysis, Caspase-3, Caspase-9, and Nf-KB mRNA expressions of those MCF-7 cells which were treated with gossypin were also conducted in order to evaluate the apoptosis or necroptosis-induced cell death. Results: In MTT experiments, it has been observed that the administration of 100 µM dose of gossypin had similar effects to the routine cisplatin administration, caused a significant decrease in cell proliferation, and increased apoptosis in the evaluations of Hoechst staining and morphology. It has been put forth that gossypin decreases the expression of CASP-3 and CASP-9 mRNA and increases the expression of NF-kB.Conclusion: Our results demonstrate that for the breast cancer cells, the 100 µM of gossypin positively affects cell death pathways due to apoptosis.
Keywords: gossypin; Apoptosis; Caspase-3; Caspase-9; NF-kB; ​Internal Diseases; İç Hastalıkları; 3. Good health